The rising burden of Alzheimer’s and other dementias: role of high fasting plasma glucose from 1990 to 2021 - Shuhua Liu; Shuhua Liu; Yuxuan Wu; Fangying Chen; Luying Han; Yu Zhang; Enqiang Chang; Enqiang Chang; Enqiang Chang; Enqiang Chang (Frontiers in Medicine)
BackgroundDementia, one of the top 10 causes of death globally, imposes significant health and socioeconomic/socioeconomic burdens, with prevalence projected to reach 82 million by 2030. High fasting plasma glucose (HFPG) is a prominent modifiable risk factor for dementia in 2021. This study aims first to examine the global trend in dementia burden and the disability-adjusted life years and death attributable to HFPG from 1990 to 2021 and second to define age-specific disparities in dementia burden among older populations.MethodsUsing data from the Global Burden of Diseases Study (GBD) 2021, this research evaluated the incidence, prevalence, deaths, disability-adjusted life years (DALYs), and HFPG-attributable burden related to Alzheimer’s disease and other dementias (ADOD). The estimated annual percentage change was calculated to qualify the burden change of ADOD.ResultsThere was a significant rise in the ADOD burden globally, with over 56.9 million prevalent cases and 2.0 million deaths in 2021. the incidence and prevalence were positively correlated with HFPG-related summary exposure value. The HFPG-attributable ADOD burden has increased worldwide over time. Globally, the 60 to 74 age groups suffered a prominent rise in the burden and HFPG-attributable burden of ADOD.ConclusionThe global burden and HFPG-attributable ADOD burden have remained prominent and have increased increase over the past 32 years. The ASIR and ASPR showed positive correlations with the SEV related to HFPG. Notably, the 60 to 74 age groups suffered a prominent rise in burden and HFPG attributable to the DALYs rate of ADOD over time. Moreover, a prominent positive correlation was observed between the incidence and prevalence rate with the SEVs related to HFPG occurred in the population aged 60 to 74 years old. Therefore, HFPG should be emphasized in strategic priorities for controlling the ADOD burden.